Phosphorus compounds advanced tools in catalysis and material Sciences - Peruzzini, Maurizio (Catalysis by Metal Complexes, 2011)
Each chapter of Phosphorus Compounds: Advanced Tools in Catalysis and Material Sciences has been carefully selected by the editors in order to represent a state-of-the-art overview of how phosphorus chemistry can provide solutions in various fields of applications. The editors have assembled an international array of world-renowned scientists and each chapter is written by experts in the fields of synthetic chemistry, homogeneous catalysis, dendrimers, theoretical calculations, materials science, and medicinal chemistry with a special focus on the chemistry of phosphorus compounds. Phosphorus Compounds: Advanced Tools in Catalysis and Material Sciences is of interest to a general readership ranging from advanced university course students to experts in academia and industry.